Using a short questionnaire of the perimenopausal fatigue scale to evaluate perimenopausal women prone to fatigue syndrome - Hsiao-Hui Chiu; Lee-Ing Tsao; Chieh-Yu Liu; Yu-Ying Lu; Whei-Mei Shih; Peng-Hui Wang (Elsevier, 2021)
Objective: Fatigue, a painful and unpleasant subjective experience, is common in perimenopausal women. Therefore, an effective tool to evaluate the fatigue-precipitating factor is important for perimenopausal women prone to fatigue syndrome. Materials and methods: This study was surveyed by short-term perimenopausal fatigue scale. The enrollment period was from November 2019 to January 2020. The subjects were perimenopausal women prone to perimenopausal fatigue. The differences between the fatigue-precipitating factors and the degrees of fatigue and disturbance were determined by one-way ANOVA and t test. Results: A total of 220 perimenopausal women with mean age of 51.3 years were included. Among these, 64.1% did not have a habit of regular exercise and 55.5% had chronic diseases. Fatigue syndrome was found in 64.1% of subjects, who were mainly presented by shoulder and neck pain and sleep problems. There were significant differences between "perimenopausal fatigue" and "duration" (p < 0.001); "with and without regular exercise" (p = 0.05); and "with and without chronic diseases" (p = 0.03). Conclusions: Our study showed the perimenopausal fatigue syndrome is more frequently found in perimenopausal women who have a co-morbidity (chronic illness) and do not have a habit of regular exercise. An early identification and prompt intervention may help perimenopausal women to deal with their fatigue syndrome. The short questionnaire perimenopausal fatigue scale seems to be useful for screening perimenopausal women prone to fatigue syndrome.